7x+y=1
adding -7x
y=1-7x
substrituting 1-7x for y in
3x+2y=-9
3x+2(1-7x)=-9
3x+2-14x=-9
-11x+2=-9
adding -2
-11x=-11
dividing by -11
x=1
sub y=1-7(1)
=1-7
=-6
solution set(1,-6)
2006-12-02 12:03:04
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
First start with the first equation and let's make it useful:
7x + y = 1 (subtract 7x from each side and get)
y = 1 - 7x
Now substitute our new equation into the second one above and get:
3x + 2y = -9
3x + 2(1 - 7x) = -9
3x + 2 - 14x = -9
Solve for x:
-11x = -11
x = 1
Substitute x = 1 into the first equation and get:
7x + y = 1
7(1) + y = 1
y = -6
So the answer is (1, -6).
Double check by seeing if the solution (1, -6) works for the second equation:
3(1) + 2(-6) = -9?
3 - 12 = -9! Yes, therefore correct!
2006-12-02 20:05:55
·
answer #2
·
answered by sep_n 3
·
0⤊
0⤋
From the first equation, we get y=1-7x. Substitute this value for y in the second equation. We get 3x+2*(1-7x)=-9. Simplifying,
3x+2-14x=-9 or -11x=-11 which gives x=1. So, y=1-7*1 or y=-6.
2006-12-02 20:11:57
·
answer #3
·
answered by greenhorn 7
·
0⤊
0⤋
If I understand the question, the substitution method is easy to use. It does require the equations to be independent from one another.
7x+y=1 and 3x+2y=-9
What you need to do first is to solve one of the two equations. For example 3x+2y=-9
y=(-9-3x)/2
Then you substitute this into the second equation
7x+(-9-3x)/2=1
simplify the equation
7x-3x/2=1
7x-3x/2=11/2 (common denominators)
14x/2 - 3x/2=11/2
multiply all portions by 2
28x-6x=22
x=1
Substitute into the original equation to find y
3x+2y=-9
3(1)+2y=-9
2y=-12
y=-6
You can then substitue y=-6 and x=1 into the other to verify
7(1)+(-6)=1
7-6=1
Hope this helps!
2006-12-02 20:12:09
·
answer #4
·
answered by amland1 2
·
0⤊
0⤋
1) 7 x + y = 1
y = 1
x = 1/7
2) 3 x + 2 y = 9
y = 9/2
x = 3
hope that helped!
if you want the y you just substitute x with 0. if you want x just substitute y with 0.
2006-12-02 20:01:17
·
answer #5
·
answered by Angels Eyes 2
·
0⤊
1⤋
7x + y = 1
y = -7x + 1
3x + 2(-7x + 1) = -9
3x - 14x + 2 = -9
-11x = -11
x = 1
y = -7(1) + 1 = -7 + 1 = -6
ANS : (1,-6)
2006-12-02 21:42:19
·
answer #6
·
answered by Sherman81 6
·
0⤊
0⤋
y= -7x+1
3x+2(-7x+1)= -9
3x-14x+2= -9
-11x= -11
x= 1
7(1)+y=1
y+7=1
y= -6
2006-12-02 20:01:58
·
answer #7
·
answered by 7
·
0⤊
0⤋